Collision and Collusion: Contrasting Representations of the Translator-Author Relationship in Two Contemporary Francophone Novels - Mével, Pierre-Alexis; Cornelio, Dawn (TTR)

(untitled) (Association canadienne de traductologie, 2016)
The article focuses on two novels (Brice Matthieussent’s 2009 Vengeance du traducteur and Jacques Poulin’s 2006 La Traduction est une histoire d’amour) which present apparently contradictory viewpoints on the role of the translator and translation through their distinctive use of both metaphors and meta-discourse on translation. Matthieussent’s novel is a revenge indeed, a postmodern tour de force where the notions of original, translation, source and target texts, author and translator, are blurred to the point of becoming irrelevant, shedding a whole new light on the concepts of faithfulness and creativity, and redefining typographical and cultural spaces. Presented as a translation by its narrator, Vengeance du traducteur is a discussion about translation, a metaphorical and symbolical deconstruction of the author-translator relationship, which creatively and cynically dissects power relations in the translation process, and questions the validity of the notions of author and translator, pointing out their absurdity. Poulin’s novel approaches the author-translator relationship more traditionally, portraying a young woman, Marine, the first-person narrator, planning to meet an author she admires, and become his translator. Though she is successful in this, few scenes focus on translation proper; instead the writer and translator must determine the owner of an abandoned kitten, using a cryptic note on its collar. They must find the right words to complete the clue, and also determine what these words truly mean. The cooperative, symbiotic connexion between the two outside their working relationship becomes a metaphor in itself for the process of translation; this in turn focuses a spotlight on the work of translating which is relegated to the background of this novel whose title announces it as central. Through careful dissection of all the novels’ elements, we will show how their mise-en-abîme of translating determines and undermines the perception and practice of literary translation.